Ethics in the Nigerian national pledge and its implications for the transformation agenda (2013)
The non-challant attitude of Nigerians on issues affecting the development of the nation has become a source of concern to all and sundry and various efforts made by successive administrations to change their Orientation at different levels of government in the country have not yielded any success. This has accounted for series of problems facing the country since independence. Several scholarly works have been done from different perspectives on issues affecting national life and how a change of attitude can be ensured among Nigerians. In this work, therefore, an attempt is made to discuss ethical issues in the National Pledge and the implications such have for the transformation agenda of the Federal Government. It is argued that if both the leaders and the followers internalise the content of the Pledge not only by reciting it but by acting the contents therein, Nigeria will be a better place for all to live and the transformation agenda of government will not to be a mirage.